2015
DOI: 10.1038/emm.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 modulates the inflammatory phenotype of intestinal myofibroblasts by targeting SOCS1 in ulcerative colitis

Abstract: Abnormal levels of microRNA (miR)-155, which regulate inflammation and immune responses, have been demonstrated in the colonic mucosa of patients with inflammatory bowel diseases (IBD), although its role in disease pathophysiology is unknown. We investigated the role of miR-155 in the acquisition and maintenance of an activated phenotype by intestinal myofibroblasts (IMF), a key cell population contributing to mucosal damage in IBD. IMF were isolated from colonic biopsies of healthy controls, ulcerative coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 50 publications
1
75
0
3
Order By: Relevance
“…We speculate that these conflicting results could be due to differences in sepsis severity and/or the time points studied. Indeed, alterations in SOCS1 expression have been associated with disease severity for several inflammatory disorders (48,(56)(57)(58). To further determine whether SOCS1 expression is increased in patients with sepsis, we employed transcriptomic analysis and found elevated levels of SOCS1 in peripheral blood cells from septic pediatric patients as compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these conflicting results could be due to differences in sepsis severity and/or the time points studied. Indeed, alterations in SOCS1 expression have been associated with disease severity for several inflammatory disorders (48,(56)(57)(58). To further determine whether SOCS1 expression is increased in patients with sepsis, we employed transcriptomic analysis and found elevated levels of SOCS1 in peripheral blood cells from septic pediatric patients as compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that aberrant miR-155 expression controlled gene expression of IL-1β and TNF-α and secretions of IL-1β and TNF-α in macrophages. It is possible that miR-155 post-transcriptionally modulates the expression of multiple target genes, including suppressor of cytokine signaling 1 (SoCS1) (16), forkhead box o3 (FoXo3a) (50), transcription factor CCAAT/enhancer binding protein β (C/EBPβ) (51), which were proven to regulate the expression of various inflammatory cytokines. Moreover, some studies have reported that TNF-α can significantly increase miR-155 expression in macrophages (52).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155, an oncogenic miRNA, is identified as a link between inflammation and cancer (14). Previous studies have found that miR-155 expression is induced by proinflammatory mediators, such as TnF-α and LPS (15), and overexpression of miR-155 has been found to elevate inflammatory cytokine production in intestinal myofibroblasts (16) and monocyte/macrophages (17,18). In addition, some studies indicate that the promoter region of pri-miR-155 contains putative NF-κB-binding sites (19,20) and miR-155 upregulation and subsequent molecular events are associated with inflammatory processes such as activation of nF-κB (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…В перспективе ученые планируют использовать этот факт в созда-нии иммуноподавляющей мишени терапии. Изме-нение уровня miR-155, которое регулирует воспали-тельные и иммунные реакции, было продемонстри-ровано в биоптатах слизистой оболочки больных ЯК [41]. В исследование были включены больные ЯК (n=8) и БК (n=8).…”
Section: лабораторные биомаркеры язвенного колитаunclassified